The Evolution of the Sonnet as a Genre: Tracing Its Development and Influential Sources - Rukhsora Imomova Akhmedovna (Indonesian Journal of Cultural and Community Development, 2024)
This article explores the evolution of the sonnet genre in Uzbek literature, tracing its origins from European literature, particularly the Petrarchan and Shakespearean traditions, to its manifestation in the works of Uzbek poets such as Barot Boyqabilov and Rauf Parfi. Utilizing comparative analysis, the study examines the structural and thematic adaptations of the sonnet form in Uzbek poetry, highlighting the influences of both European models and indigenous innovations. Results demonstrate the diverse approaches adopted by Uzbek poets in reimagining the sonnet, showcasing a synthesis of traditional forms with unique cultural expressions. This research sheds light on the dynamic interplay between global literary traditions and local artistic practices, contributing to a deeper understanding of cross-cultural literary exchange and innovation. Highlights: Cross-Cultural Sonnet Adoption: Sonnet's European origin influenced Russian, Turkish, and Uzbek poetry, demonstrating its cross-cultural adaptability. Literary Influence and Innovation: Uzbek poets like Boyqabilov and Parfi expanded the sonnet genre, inspired by Petrarch and Shakespeare. Sustaining Tradition and Individual Expression: Uzbek poets blended European tradition with personal themes, enriching Uzbek poetry's cultural tapestry. Keywords: Sonnet, Petrarch's Style, Genre Transformation